Antibacterial and Antioxidant Activites of Secondary Metabolites of Endophytic Fungus Stemphylium radicinum (Meier, Drechs and Eddy) - Hateet, Rashid Rahim (Iraqi Journal of Science, 2022)
AbstractEndophytic fungi are gaining interest as sources of novel bioactive metabolites.The study was carried out to screen and isolate endophytic fungus.An endophyticfungus isolated from root of calyptous plant .The fungus was identified asStemphylium radicinum (Meier, Drechs and Eddy)based on morphologicalcharacterization. Fungal secondary metabolites was carried out by ethyl acetatesolvent.The antibacterial activity was tested against five bacterial isolates.Esherichia coli, Staphylococcus aureus, Proteus vulgaris, Klebsiella pneumonia andStreptococcus pyogenes by using a disc diffusion technique. The inhibition zonesexhibited by Fungal secondary metabolites were ranged between 22.5-35.5 mm.Minimum inhibitory concentration MIC test revealed that the extract of S. radicinumexhibited a minimal inhibition values ranging between 25.0-100 ug/ml againstbacterial strains .A verification of non toxicity of the fungal secondary metabolitesagainst human blood revealed a negative test. Active compounds of the fungalsecondary metabolites involves Tannins, phenols and amino acid .The antioxidantactivity was analyzed using2,2-diphenyl-1-picrylhydrazyl (DPPH) scavengingassays .The metabolite produced by the fungi could be an alternative source ofantimicrobial against clinical pathogens.